A lét és a semmi határán – Mrs. Ramsay test-terei - Moise, Gabriella (Studia Litteraria, 2011)
The structural plasticity of Virginia Woolf ’s To the Lighthouse defines the figure of Mrs. Ramsay, one of the central characters of the novel, as a spatio-corporeal entity. She occupies a transitory space in the texture of the novel, frequently being associated with the window, a trope of mediation and liminality itself. The ambiguity of her status rests in her incessant inclination to unite the family members and guests and to create stability and order while she herself withdraws into her “wedge-shaped core of darkness” remaining inaccessible and invisible for others. Mrs. Ramsay’s bodily presence appears analogous with a whole series of literal and imaginary architectural constituents and architectonic forms (windows, stairs, the drawing room steps, the lighthouse, the dome shaped hive, the tombs of kings, a cathedral-like space) primarily, through her identification with the Ramsays’ summer cottage, with the interiority of its domestic milieu. This, however, is expanded by her subsequent identification with the Lighthouse, a minimalist, emphatically vertical and guiding architectural design of the novel. Thus, Mrs. Ramsay emerges as an existential referential point in Sartre’s term. For Sartre,—as he argues in his Being and Nothingness— the upsurge of the self rests on the demarcation of an existential distance from the things of the world and the surpassing of one’s own body as yet another necessary obstacle. Mrs. Ramsay, as the basis of the spatio-corporeal existence, serves as space proper for the others: simultaneously, offering the potential for spatial embeddedness, as well as the delineation of corporeal distances within the network of things and bodies.